1998
DOI: 10.1159/000007512
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Control of the Ovine Gallbladder: Ultrastructural and Functional Study

Abstract: The purpose of this study was to investigate the ultrastructure of the local nerve supply of ovine gallbladders as well as the functional characteristics of inhibitory nerves. We used electron microscopy of thin sections of ovine gallbladders and in vitro isometric tension recording using gallbladder strips. Specifically, we measured contractile and inhibitory responses induced by transmural electrical field stimulation (EFS). We found a ganglionated plexus with intramural nerve cells and interconnecting axons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Previous pharmacological data support our finding, showing a neurally mediated inhibition of the gall bladder musculature by NO 1314 This was initially demonstrated in vitro using human gall bladder muscle strips where TTX sensitive, EFS evoked relaxations were blocked by l -nitroarginine 13. More recent studies have demonstrated a similar mechanism in the guinea pig,24sheep,14 and human25 gall bladder.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Previous pharmacological data support our finding, showing a neurally mediated inhibition of the gall bladder musculature by NO 1314 This was initially demonstrated in vitro using human gall bladder muscle strips where TTX sensitive, EFS evoked relaxations were blocked by l -nitroarginine 13. More recent studies have demonstrated a similar mechanism in the guinea pig,24sheep,14 and human25 gall bladder.…”
Section: Discussionsupporting
confidence: 88%
“…14 This was initially demonstrated in vitro using human gall bladder muscle strips where TTX sensitive, EFS evoked relaxations were blocked by l -nitroarginine 13. More recent studies have demonstrated a similar mechanism in the guinea pig,24sheep,14 and human25 gall bladder. Notably, these studies did not characterise the source of the inhibitory innervation.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, more careful pharmacological analyses should be performed to establish the role of muscarinic receptor subtypes on the MR. The inhibitory action of hexamethonium can be exerted due to its binding to nicotinic receptors present in the gallbladder ganglia (Khoursheed et al, 1998).…”
Section: Discussionmentioning
confidence: 99%